Keragaan dan Mutu Buah Cabai pada 2 Jenis lahan Ultisol di Kabupaten Bangka Barat - Amilia, Rossa; Mustikarini, Eries Dyah (Jurnal Agroekoteknologi, 2024)
Cayenne pepper is a horticultural crop commodity. Cayenne pepper cultivation on ultisol land is an effort to utilize marginal land as an agricultural sector. Cayenne pepper development activities are carried out incorrectly to maintain the source of availability. The purpose of this study was to determine the morphology of the types of cayenne pepper on ultisol land in West Bangka Regency, to determine the quality and level of productivity of cayenne pepper types on ultisol land in West Bangka Regency and to determine the content contained in cayenne pepper. This research was conducted at 2 (two) locations for cayenne pepper cultivation in Kelapa Village and Tebing Village, Kelapa District, West Bangka Regency, Bangka Belitung Islands Province in February - April 2023. The results of the study on cayenne pepper of the Cakra variety had better morphology in character plant height, branch height, fruit length, leaf length, fruit diameter and leaf width. The production of cayenne pepper cultivation of the Cakra variety in Tebing Village yields 7 tonnes/ha. Cayenne pepper of the Bogor variety cultivated in Kelapa Village has a high vitamin C content of 13% and cayenne pepper of the Bogor variety cultivated at Tebing Village has a high Total Dissolved Solids of 5 brix.Keywords:  Bogor, Cakra,  Cayenne Pepper, Ultisol Land, West Bangka